Survey of terahertz communication technology - Sha XIE; Haoran LI; Lingxiang LI; Zhi CHEN; Shaoqian LI (Tongxin xuebao)
There are some challenges that need to be overcome before terahertz communication technology is widely applied,such as large propagation attenuation in the air and short transmission distance.Research progresses of terahertz channel,such as terahertz channel model,terahertz channel measurement and terahertz channel estimation,were first reviewed.Based on these characteristics of terahertz channel,the underlying problems in basic single-user communication scenarios and more complicated multi-user communication scenarios were respectively analyzed.For each scenario possible solutions were concluded.Last but not least,some prospect future research directions on terahertz communications were discussed.